Analysis of Organizational Citizenship Behavior in School - Syafa’at Ariful Huda; Chairunnisa Chairunnisa; Purwani Puji Utami (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
The purpose of this research is to investigate the influence of trust and job satisfaction on teachers’ Organizational Citizenship Behavior in Junior High School of Private Districts Tangerang. The research used survey method applied in testing hypothesis. Technique of data collecting used questionnaire. There were 273 teachers used as samples and selected by simple random sampling. For data analysis Structural Equation Model (SEM) was used to get more detailed results related to trust, job satisfaction and Organizational Citizenship Behavior variables. The result of the research indicated that 1) there was a direct positive effect of trust to teachers’ Organizational Citizenship Behavior; 2) there was a direct positive effect of job satisfaction to teachers’ Organizational Citizenship Behavior; and 3) there was a direct positive effect of trust to job satisfaction.